Gendered Vulnerabilities in Disaster Responses: A Case Study of Majuli Island, Assam (Indian Journal of Social Science and Literature (IJSSL), 2024)
This study employs a qualitative research methodology to study the gender disparities in disaster responses, focusing on the case study of Majuli Island in Assam, India, to provide nuanced insights into the distinct vulnerabilities experienced by women, particularly in the context of floods. Through an in-depth exploration of social norms, behavioural restrictions, and resource allocation practices, the research elucidates how women’s roles as caregivers and providers constrain their mobility and exacerbate their susceptibility to harm. The gendered ramifications of disasters on health, encompassing reproductive health issues and malnutrition, are underscored, alongside the psychological and physiological impacts that precipitate enduring mental anguish and heightened risks of violence and abuse. The findings underscore the imperative for gender-sensitive approaches to disaster preparedness, response, and recovery, advocating for comprehensive strategies that foreground women’s safety, well-being, and empowerment. By adopting a qualitative research methodology grounded in descriptive investigation, the study delves deeply into the lived experiences of communities grappling with disaster risks, offering invaluable insights for policymakers, practitioners, and communities striving to foster inclusive and resilient societies.